Pilot-scale co-enrichment of beta-casein and whey protein from skim milk via ceramic membrane cold microfiltration - Sijia Song; Yingying Lin; Peng Xue; Kaibo Wang; Yi Xue; Yun Chen; Wentao Qian; Aiping Liu; Huiyuan Guo (Applied Food Research)
Beta-casein (β-CN) and whey protein are highly promising ingredients for infant milk formula (IMF), and their addition to IMF can further bridge the nutritional gap between IMF and human milk. At present, there are few studies on pilot-scale co-enrichment of β-CN and whey protein, which is crucial for industrial-scale production. This study investigated the optimization of pilot-scale process parameters for the co-enrichment of β-CN and whey protein through cold microfiltration. A pilot-scale 3-stage ceramic membrane filtration system was used, and two different membrane pore sizes, 0.14 μm and 0.2 μm, were evaluated. The results demonstrated that the 0.14 μm ceramic membrane exhibited higher filtration efficiency than the 0.2 μm membrane. Additionally, the effects of transmembrane pressure (TMP, 50–140 kPa), volume concentration factor (VCF, 2–3.5), and filtration temperature (10–25 °C) on process performance and protein-enrichment were assessed using the 0.14 μm membrane. The results indicated that the enrichment rate increased with the rise in TMP, VCF and temperature. Filtration efficiency also increased with TMP and temperature; however, it initially increased and then decreased as the VCF increased. The optimal TMP, VCF, and temperature for high-efficiency enrichment of β-CN and whey protein were 140 kPa, 3, and 15 °C, respectively. These findings will provide valuable guidance for the future industrial-scale production of β-CN and whey protein.